New Ocnerodrilidae genera, species and records from Brazil (Annelida: Crassiclitellata) - James, Samuel W.; Bartz, Marie L.c.; Brown, George G. (Zootaxa, 2023)
We describe three new species of Eukerria, six of Kerriona, one of Ocnerodrilus and two of Belladrilus (Clitellata: Ocnerodrilidae) from Brazil, mostly from wet habitats including bromeliad leaf axils, plus some from forest soils in Bahia state. We also provide new morphological and distribution data on Kerriona luederwaldti Michaelsen, 1924. We describe the new genus Pauqueba and its two new species, both from bromeliad leaf axils and forest floor litter in the state of Bahia. It has two pairs of calciferous glands, the balantine reduction of the male terminalia but spermathecae in ix, and no gizzard. The new genus Parabauba found in deeper (30 cm) soil layers is distinctive for the combination of two pairs of calciferous glands, a large gizzard in v, acanthodriline male terminalia, and no typholosole. The new genus Diplomoela from a mesic soil in Bahia is meronephric, unusually large for the Ocnerodrilidae, and has two well-developed gizzards.